A two-dimensional polymer with nonlinear optical properties and a synthesis method thereof
By spreading surfactant on the water surface and performing two-dimensional polymerization, a two-dimensional polymer film with nonlinear optical properties is prepared, which solves the challenge of preparing large-area and uniform films and achieves excellent third-order nonlinear optical properties .
Patent Information
- Application Number
- CN202311254833.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-09-26
AI Technical Summary
Preparing two-dimensional polymer crystalline films with nonlinear optical properties with large area and uniform thickness is still a major challenge, especially in third-order nonlinear optical applications, such as low transmittance and scattering.
By spreading a single layer of surfactant on the water surface, and under its adsorption, ligand 1 and ligand 2 are added to the aqueous phase and undergoing two-dimensional polymerization, a two-dimensional polymer film with nonlinear optical properties is obtained. The method involves dissolving ligand 1 with triflate under acidic conditions and orderly arrangement of ligand 2 by electrostatic interactions, followed by injecting ligand 2 into the aqueous phase for two-dimensional polymerization.
The two-dimensional polymer film prepared by this method is uniform, continuous and has good light transmittance, which solves the problems of low transmittance and scattering in third-order nonlinear optical applications, and has excellent third-order nonlinear optical properties.
Smart Images

Figure CN117264156B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonlinear optics and relates to a two-dimensional polymer with nonlinear optical properties and a synthesis method thereof. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Nonlinear optics (NLO) is a branch of modern optics that studies the nonlinear phenomena and applications of media under the action of strong coherent light. Traditionally, the nonlinear optical materials that have been studied more are inorganic crystals, such as perovskite-type, borate series materials, inorganic semiconductors, etc., organic small molecules such as porphyrin, phthalocyanine, molecules with macrocyclic conjugated π structures, azo compounds, and polymers: conjugated polymers, etc. The stable chemical properties of inorganic nonlinear optical materials and the nonlinear effects produced by the structural characteristics of the materials themselves can meet the needs of some applications, but this type of material will produce a lot of absorption and heat loss when producing nonlinear effects, and the light response time is long. Compared with inorganic materials, organic materials have the advantages of fast response time and high optical damage threshold, but their thermal stability is low and the processability is poor. In recent years, more and more two-dimensional materials have been used in the field of nonlinear optics, such as graphene, C3N4, Mexeen, etc. Traditional two-dimensional materials have low mechanical strength and thermochemical stability, and the instability of the materials has significantly limited the practical application of nonlinear optical properties. Two-dimensional polymers (2DPs) are long-range ordered organic two-dimensional crystalline materials composed of small molecular repeating units connected by covalent bonds, with a single atom or monomer thickness. Compared with traditional organic materials, two-dimensional polymers have significant advantages in higher mechanical strength, thermochemical stability and extended conjugation. As nonlinear optical materials, two-dimensional polymers show great application potential in high-tech fields such as bioimaging, chemical sensors, optical data storage, laser protection, and controllable intelligent optoelectronic devices. Moreover, the pores present in the framework provide a simple way to introduce functional groups without changing the structure, allowing fine-tuning of the NLO response. However, most two-dimensional polymers are synthesized in powder form. When studying their third-order nonlinear optics, the powder usually needs to be dispersed in an organic solvent, which is prone to powder agglomeration and deposition during the test, causing the sample to scatter into the laser, which limits its application in nonlinear optics.
[0004] Currently, the preparation of large-area, uniform-thickness, two-dimensional polymer crystalline films with nonlinear optical properties remains a major challenge. Summary of the invention
[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a two-dimensional polymer film with nonlinear optical properties and a synthesis method thereof.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] In a first aspect, the present invention provides a two-dimensional polymer film material having nonlinear optical properties, the structural formula of which is:
[0008] M is 2H or Zn.
[0009] In a second aspect, the present invention provides a method for synthesizing a two-dimensional polymer film having nonlinear optical properties, comprising the following steps:
[0010] Spreading a monolayer of surfactant on the water surface;
[0011] Adding ligand 1 solution into the water phase, so that ligand 1 is orderly arranged on the surface of the water under the adsorption of the surfactant;
[0012] Inject ligand 2 into the water phase, ligand 2 diffuses into the ordered ligand 1, undergoes two-dimensional polymerization, and obtains a two-dimensional polymer film;
[0013] The structural formula of the ligand 1 is shown in Formula I; the structural formula of the ligand 2 is shown in Formula II:
[0014] M is 2H or Zn;
[0015] The present invention uses 5,10,15,20-tetrakis(4-aminophenyl)-21H,23H-porphyrin (TAPP) or 5,10,15,20-tetrakis(4-aminophenyl)-porphyrin zinc (TAPPZn) and 4,4'-(diazene-1,2-diyl)benzaldehyde as ligands to prepare two-dimensional polymer materials with different nonlinear responses. A quartz sheet is used as a solid substrate to fish out the film. The covalent organic framework film prepared by this method is uniform, continuous, and has good light transmittance, which solves the key problems of low transmittance and high scattering encountered in third-order nonlinear optical applications. In addition, the large π-electron conjugation and narrow optical band gap of the two-dimensional polymer enhance the intramolecular charge transfer of the two-dimensional polymer structure, making it have good application prospects in the field of third-order nonlinear optics.
[0016] In some embodiments, the surfactant is a surfactant that has electrostatic attraction with ligand 1 and ligand 2.
[0017] Preferably, the surfactant is a long-chain alkyl anionic surfactant with a sulfate ion as the head group.
[0018] Preferably, the surfactant is sodium oleyl sulfate (SOS). Surfactants such as sodium dodecylbenzene sulfonate and other long-chain alkyl anionic surfactants with sulfate ions as head groups are feasible, and films with excellent morphological uniformity can be obtained, among which sodium oleyl sulfate has the best effect. This can be attributed to the fact that the sulfate group has the highest negative charge density and forms a stable surfactant monolayer film on the water surface, which is conducive to co-assembly with porphyrin through electrostatic interaction, inducing long-range orderly arrangement of porphyrin monomers in the two-dimensional direction.
[0019] In some embodiments, the ligand 1 solution is a trifluoromethanesulfonic acid solution of ligand 1. Trifluoromethanesulfonic acid is a catalyst for protonation. Protonation is to dissolve ligand 1 in trifluoromethanesulfonic acid. Thus, under acidic conditions, the amino N on the tetraphenylaminoporphyrin is protonated and positively charged, and combines with the anionic surfactant to generate electrostatic interaction.
[0020] In some embodiments, in the aqueous phase, the molar ratio of Ligand 1 to Ligand 2 is 1:3.5-4.5.
[0021] Preferably, in the aqueous phase, the molar ratio of ligand 1 to ligand 2 is 1:4.
[0022] In some embodiments, the temperature of the two-dimensional polymerization is 45-55° C., and the time of the two-dimensional polymerization is 5-7 days.
[0023] Preferably, the temperature of the two-dimensional polymerization is 50°C.
[0024] In a third aspect, the present invention provides an application of the two-dimensional polymer film having nonlinear optical properties in the preparation of a third-order nonlinear optical device.
[0025] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0026] The present invention provides a two-dimensional polymer with nonlinear optical properties and a synthesis method thereof, so as to overcome the technical problems of unstable nonlinear absorption performance of current two-dimensional polymer films and complicated experimental operation. Tetraphenylaminoporphyrin with a highly delocalized 18-pair electron conjugated system and azo functional groups are selected as building units, and by introducing π conjugated structure and -N=N- into the two-dimensional polymer, the conjugation effect of π orbital expands the charge distribution range and improves the high mobility of electrons. The ordered conjugated structure makes it have a lower optical band gap and excellent third-order nonlinear optical performance, which is better than the third-order nonlinear optical materials reported recently. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0028] Figure 1 A schematic diagram of the synthesis of a two-dimensional polymer film material according to an embodiment of the present invention;
[0029] Figure 2 The attenuated total reflection infrared (ATR-IR) spectra of the two-dimensional polymer film materials 2D-TAPP (b) and 2D-TAPPZn (a) in Examples 1 and 2 of the present invention are shown;
[0030] Figure 3 The Raman spectra of the two-dimensional polymer thin film materials 2D-TAPP (b) and 2D-TAPPZn (a) in Examples 1 and 2 of the present invention;
[0031] Figure 4 The UV-visible spectra of the two-dimensional polymer thin film materials 2D-TAPP (b) and 2D-TAPPZn (a) in Examples 1 and 2 of the present invention;
[0032] Figure 5 Optical microscope images of the two-dimensional polymer thin film materials 2D-TAPPZn-50°C (a), 2D-TAPPZn-RT (b), 2D-TAPP-50°C (c), and 2D-TAPP-RT (d) in Examples 1 and 2 of the present invention;
[0033] Figure 6 Transmission electron micrographs of the two-dimensional polymer thin film materials 2D-TAPPZn-50°C (a), 2D-TAPPZn-RT (b), 2D-TAPP-50°C (c), and 2D-TAPP-RT (d) in Examples 1 and 2 of the present invention;
[0034] Figure 7 These are third-order nonlinear performance diagrams of the two-dimensional polymer film materials 2D-TAPPZn-50℃(a), 2D-TAPPZn-RT(b), 2D-TAPP-50℃(c), and 2D-TAPP-RT(d) in Examples 1 and 2 of the present invention. DETAILED DESCRIPTION
[0035] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0036] The present invention will be further described below in conjunction with the embodiments.
[0037] Example 1
[0038] Preparation of 2D-TAPP, a two-dimensional polymer with nonlinear optical properties.
[0039] See also Figure 1 , using amphiphilic self-assembled monolayer as template, a monolayer of surfactant SOS was spread on the water surface, and then ligand 1 (TAPP, 1μmol, 1ml) dissolved in trifluoromethanesulfonic acid (TfOH, 1M) was added to the water phase. Due to electrostatic interaction, ligand 1 adsorbed with the surfactant monolayer, so that ligand 1 was orderly arranged on the water surface. Next, ligand 2 (Dbzd, 4μmol, 1ml) was injected into the water phase and then diffused into the pre-organized ligand 1, initiating two-dimensional polymerization on the water surface. The polycondensation reaction was maintained at 50°C and room temperature for 5 days and 7 days respectively. A 2DP-TAPP film was obtained on the water surface.
[0040] The prepared 2DP-TAPP film was placed on copper foil for attenuated total reflection infrared (ATR-IR) spectroscopy testing;
[0041] The prepared 2DP-TAPP film was placed on a quartz plate to test the UV and nonlinear optical properties;
[0042] The prepared 2DP-TAPP film was placed on a silicon wafer for Raman spectroscopy testing and optical microscopy observation;
[0043] The prepared 2DP-TAPP film was placed on a copper grid for transmission electron microscopy observation.
[0044] Example 2
[0045] Preparation of 2D-TAPPZn two-dimensional polymer with nonlinear optical properties
[0046] like Figure 1 As shown, a monolayer of surfactant SOS was spread on the water surface using amphiphilic self-assembled monolayer as a template, and then ligand 1 (TAPPZn, 1 μmol, 1 ml) dissolved in trifluoromethanesulfonic acid (TfOH, 1 M) was added to the water phase. Due to electrostatic interaction, ligand 1 adsorbed with the surfactant monolayer, so that ligand 1 was orderly arranged on the water surface. Next, ligand 2 (Dbzd, 4 μmol, 1 ml) was injected into the water phase and then diffused into the pre-organized ligand 1, initiating two-dimensional polymerization on the water surface. The polycondensation reaction was maintained at 50°C and room temperature for 5 days and 7 days, respectively. A 2DP-TAPPZn film was obtained on the water surface. The film was scooped out for attenuated total reflection infrared (ATR-IR) spectroscopy test on copper foil, ultraviolet and nonlinear optical performance test on quartz wafer, Raman spectroscopy test and optical microscope observation on silicon wafer, and transmission electron microscope observation on copper mesh.
[0047] Product characterization and performance testing
[0048] like Figure 2 As shown, the attenuated total reflectance infrared spectroscopy (ATR-IR) showed that the polymer -1 -CHO disappears, ~3300cm -1 The disappearance of -NH2 and ~1680cm -1 The formation of C=N bond at , indicating the successful formation of imine bond.
[0049] like Figure 3 As shown in Figure 2, the Raman spectra of the ligand and the two-dimensional polymer were studied by measuring the changes in the bands corresponding to amine, aldehyde, and imine groups through laser confocal Raman spectroscopy. The Raman spectra showed that the ligand 1 had a peak at ~1280 cm -1 The NH bending band at 1700 cm-1 and the ligand 2 -1 Both bands disappeared in the 2DP spectrum, indicating that the amine and aldehyde groups have been successfully converted in the two-dimensional polymer.
[0050] like Figure 4 As shown, the 2D polymer was characterized by UV-visible spectroscopy. The UV-visible spectrum showed characteristic Soret (S) bands at 428 nm (TAPP), 440 nm (TAPPZn) and Q bands at 528, 580 and 668 nm, which corresponded to the porphyrin units, further confirming their presence in the 2D polymer. Compared with the S band of ligand 1, the S band of the 2D polymer was red-shifted by 15-20 nm, indicating the presence of extended conjugation in the 2D polymer.
[0051] like Figure 5 As shown, the film remained stable and uniform as observed by optical microscopy.
[0052] like Figure 6 As shown, the morphology of the film was observed by transmission electron microscopy, and a layered structure was identified at the edge of the film, indicating that the synthesized two-dimensional polymer has multilayer characteristics.
[0053] like Figure 7 As shown in the figure, the nonlinear optical properties of the two-dimensional polymer were studied by using nanosecond Z scanning technology at an excitation wavelength of 532nm using an open hole Z scan. The laser is Nd:YAG, and the laser pulse energy is 1 to 8μJ. The figure shows the third-order nonlinear experimental data and fitting curves at different pulse energies, showing excellent third-order nonlinear absorption characteristics. The nonlinear absorption coefficient (β) is in the range of 1.84 to 7.1×10 -7 cm / GW.
[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A two-dimensional polymer film material with nonlinear optical properties, characterized in that: Its structural formula is: M is 2H or Zn.
2. The method for synthesizing a two-dimensional polymer film having nonlinear optical properties according to claim 1, characterized in that: The steps include: Spreading a monolayer of surfactant on the water surface; Adding ligand 1 solution into the water phase, so that ligand 1 is orderly arranged on the surface of the water under the adsorption of the surfactant; Inject ligand 2 into the water phase, ligand 2 diffuses into the ordered ligand 1, undergoes two-dimensional polymerization, and obtains a two-dimensional polymer film; The structural formula of the ligand 1 is shown in Formula I; the structural formula of the ligand 2 is shown in Formula II: M is 2H or Zn; When M is 2H, the structural formula of ligand 1 is When M is Zn, the structural formula of ligand 1 is 3. The synthesis method according to claim 2, characterized in that: The surfactant is a surfactant that has electrostatic attraction with the ligand 1 and the ligand 2.
4. The synthesis method according to claim 3, characterized in that: The surfactant is a long-chain alkyl anionic surfactant with sulfate ion as the head group.
5. The synthesis method according to claim 3, characterized in that: The surfactant is sodium oleyl sulfate.
6. The synthesis method according to claim 2, characterized in that: The ligand 1 solution is a trifluoromethanesulfonic acid solution of ligand 1.
7. The synthesis method according to claim 2, characterized in that: In the aqueous phase, the molar ratio of ligand 1 to ligand 2 is 1:3.5-4.
5.
8. The synthesis method according to claim 7, characterized in that: In the aqueous phase, the molar ratio of ligand 1 to ligand 2 is 1:
4.
9. The synthesis method according to claim 2, characterized in that: The temperature of the two-dimensional polymerization is 45-55° C., and the time of the two-dimensional polymerization is 5-7 days.
10. The synthesis method according to claim 9, characterized in that: The temperature of the two-dimensional polymerization was 50°C.
11. Use of the two-dimensional polymer film with nonlinear optical properties as claimed in claim 1 in the preparation of third-order nonlinear optical devices.
Citation Information
Patent Citations
Photoelectric conversion element and solar battery
JP2014044918A
Method for the synthesis of a two-dimensional or quasi-two-dimensional polymer film, the two-dimensional or quasi-two-dimensional polymer film and the use
US20220325053A1